Medical‐surgical nurses' experiences as first responders during deterioration events: a qualitative study. Issue 21 (15th August 2016) - Hart, Patricia L.; Spiva, LeeAnna; Dolly, Lonnie; Lang‐Coleman, Kristen; Prince‐Williams, Nadia
Abstract : Aim and objective: To explore and understand the experiences of medical‐surgical nurses as first responders during clinical deterioration events. Background: Nurses are key players in identifying and responding to deterioration events to escalate the level of care essential to address specific needs of patients. Delays in recognising signs and symptoms of patient deterioration and activation of Rapid Response Teams have been linked to a lack of nontechnical skills (leadership, teamwork, situational awareness) resulting in increased patient morbidity and mortality. Design: A descriptive, qualitative approach was used. Methods: A purposive sample of 28 medical‐surgical nurses was recruited and interviewed from an integrated healthcare system located in the USA. Interviews were conducted from October 2014–February 2015. Interviews were audio recorded and transcribed verbatim. Transcripts were entered into MaxQDA. The constant comparative method was used for data analysis. Results: Three patterns emerged from the data analysis: Recognising and Responding to the Event, Managing the Event and Challenges Encountered during the Event . From the patterns, seven themes emerged. Themes for pattern one, Recognising and Responding, were early warning signs, continuity in patient care assignments and intuition. Themes for pattern two, Managing the Event, were cognitive, technical and behavioural skills. The theme for pattern three, Challenges Encountered during the Event, was work environment complexity. Conclusion: Listening to the stories of medical‐surgical nurses provided insight into how they recognised and managed patients experiencing clinical deterioration events. Furthermore, insight into the challenges that medical‐surgical nurses encountered in caring for deteriorating patients were identified. Relevance to clinical practice: Implication for practice in the areas of continuity of patient assignments, formal clinical deterioration education, work environment and team collaboration and communication was presented.